Scaling Direct Air Capture (DAC): A moonshot or the sky's the limit? - Peter Webb; Hasan Muslemani; Mark Fulton; Nigel Curson (The Oxford Institute for Energy Studies, 2023)
Direct Air Capture technology coupled with geological storage ('DACS', also 'DACCS') has recently emerged as one of the main carbon dioxide removal (CDR) needed to reach net-zero targets. If deployed at scale, DACS would result in 'negative emissions' which would preclude the need for riskier options to abate emissions, such as geo-engineering solutions. This study assesses the technical, engineering, materials and resource requirements needed to take the technology from its current megatonne level of deployment to the gigatonne level needed to achieve climate targets by 2050.
Keywords: 330; carbon removal; CDR; Climate Action; DAC; DACS; Direct Air Capture; net-zero